PEMAKAIAN KONTRASEPSI SUNTIK AKAN MEMPENGARUHI BERAT BADAN AKSEPTOR KB SUNTIK DI KOTA BARU DRIYOREJO - Nurul Kamariyah (Universitas Nahdlatul Ulama Surabaya, 2014)
Acceptor use of contraceptive injection most complain weight increased. Although knowing acceptor increased weight, they keep use contraceptive injectable. Therefore, this study was purposed to find out the correlation between the use of contraceptive injection and the body weight change happening to the acceptors. The design of study was analytic-cross sectional. The population involved all acceptors using contraceptive injection for more than one year,totally 89 people. 74 respondents were chosen as the samples by using probability sampling in which the simple random sampling technique was applied in this study. Variable of this research are independent (the use of contraceptive injection) and dependent (the body weight change). The data were collected by using family planning registration card, observation sheets, and a weight scale. The data were processed by editing, coding and tabulating. The data analysis was done by using Mann-Whitney’s test with the significance level α = 0.05. The result of analysis showed that p = 0.007 < α = 0.05 which meant that H0 was rejected most of the acceptors having three-month contraceptive injection had weight gain. describing that there was a correlation between the use of contraceptive injection and the body weight change happening to the acceptors. The conclusion of this study was that the use of contraceptive injection containing hormone affect the change of body weight. Thus, the correct counseling, information, and education to the acceptors contraceptive injection to choice non hormonal contraceptive if experienced excessive weight gain.